Phytobiotic effects of Guinea grass supplementation on production and health performances of coloured-broilers - Yee Lyn Ong; Eric Lim Teik Chung; Nazri Nayan; Muhamad Faris Ab Aziz; Faez Firdaus Abdullah Jesse; Awis Qurni Sazili (Italian Journal of Animal Science)
Growing concerns about antibiotic resistance in the livestock industry have prompted researchers to explore alternative solutions. This study investigated the effects of Megathyrsus maximus as a phytobiotic supplement on the production performance and health of Sasso broilers raised in tropical environments. 216 Sasso mixed-sex broiler chicks were randomly assigned to six treatment groups (six replicates per treatment): Treatment 1 (T1) as a negative control (no antibiotics), Treatment 2 (T2) as a positive control (100 mg/kg oxytetracycline), and Treatments 3–6 received 1.25, 2.50, 3.75, and 5.00 g/kg of M. maximus grass meal on top the basal diet, respectively, without antibiotics. At day 56, broilers in T6 had the highest final body weight (1.87 kg) and superior FCR of 1.93. Nutrient digestibility was optimised at higher doses of M. maximus, with the highest CP (67.68%) and EE (74.50%) digestibility in the T6 group (p < 0.001). Megathyrsus maximus also improved intestinal morphology, with higher VH:CD in all segments. However, microbial counts and carcase characteristics remained largely unaffected, though meat quality was significantly improved in terms of reduced drip loss and shear force at supplementation levels of 5.00 g/kg. Blood biomarkers analysis and decreased liver enzyme activity in the M. maximus groups, particularly in T6, suggests lowered inflammation and enhanced liver function. This study concludes that M. maximus supplementation, particularly at the highest inclusion level (T6) shows potential as an effective antibiotic replacement in tropical poultry production.